The Impact of Resonance Frequency Breathing on Measures of Heart Rate Variability, Blood Pressure, and Mood - Steffen, Patrick R.; Austin, Tara; DeBarros, Andrea; Brown, Tracy (Frontiers in Public Health, 2017)
Heart rate variability biofeedback significantly improves heart rate variability. Breathing at resonant frequency (approximately 6 breaths per minute) constitutes a key part of heart rate variability biofeedback training and is hypothesized to be a pathway through which biofeedback improves heart rate variability. No studies to date, however, have experimentally examined whether resonant frequency (RF) breathing impacts measures of heart rate variability. The present study addressed this question by comparing three groups: the RF group breathed at their determined RF for 15 minutes; the RF+1 group breathed at 1 breath per minute higher than their determined RF for 15 minutes; and the third group sat quietly for 15 minutes. After this 15-minute period, all groups participated in the Paced Auditory Serial Addition Task (PASAT) for 8 minutes, and then sat quietly during a 10-minute recovery period. Heart rate variability, blood pressure, and mood were measured throughout the experiment. Groups were not significantly different on any of the measures at baseline. After the breathing exercise, the RF group reported higher positive mood than the other two groups, and the RF group showed a significantly higher LF/HF HRV ratio relative to the control group, a key goal in heart rate variability biofeedback training (ps < .05). Additionally, the RF group showed lower systolic blood pressure during the PASAT and during the recovery period relative to the control group, with the RF+1 group not being significantly different from either group (ps < .05). Overall, RF breathing appears to play an important role in the positive effect heart rate variability biofeedback has on measures of heart rate variability.